Multiple interpretations of images of Spain in vocal works of composers: Comparative analysis of romances based on Pushkin's poems - Boiko, Valentina L. (Russian studies in culture and society, 2025)
Chamber vocal lyrics of Russian composers have been the subject of study for many researchers more than once. In this sense, the diversity of approaches and methods of study becomes interesting. One of them is the method of comparative analysis, which examines vocal works of different composers written to the same poem. The poem by A.S. Pushkin "I am here, Inezilla!" was a source for the inspired embodiment of this romantic plot in music by many composers. And if the musical interpretation of this opus by M. Glinka, A. Dargomyzhsky, N. Medtner, V. Shebalin and T. Khrennikov is reflected both in the works of theoretical musicologists and in the concert practice of musicians-performers, then the romances of composers V. Kosenko and V. Deshevov are practically unknown. The aimof the study is to analyze multiple authors' interpretations and creative solutions in composing romances based on A.S. Pushkin's poem "I Am Here, Inezilla!". Materials and methods. The material for the study is the romances composed by various composers based on Alexander Pushkin's poem “I am here, Inesilla!” The main research method is comparative analysis, which allows comparing different phenomena in order to identify their common characteristics and differences. Results. The author of the study summarized the theoretical and practical experience of working with both well-known romances (M. Glinka, A. Dargomyzhsky, N. Medtner) to the poem by A.S. Pushkin, and those that are practically never heard on stage (V. Deshevov, V. Kosenko, V. Shebalin, T. Khrennikov). The Spanish color of the Pushkin’s poem is realized in the romances in various ways. Conclusion. In the composer’s practice the creation of the artistic image is facilitated by a variety of factors, among which are the choice of means of expression, the ability to build the process of the communication word-music, the using arsenal of the methods of composer’s technology which are fundamental.